Imaginarios testimoniales en escritoras argentinas contemporáneas (Gabriela Cabezón Cámara, Selva Almada, Belén López Peiró) (Altre Modernità, 2021)
In addition to exploring the ways Le viste la cara a Dios by Gabriela Cabezón Cámara, Chicas muertas of Selva Almada and ¿Porqué volvías cada de verano? of Belén López Peiró they renew the features of the testimony and / or related genres, I am interested here, on the one hand, to review how the imaginaries of sexist sexual violence displayed by them enter into connection with the universe of seventies events and stories; on the other, to identify the different images of resistance that they form — linked to a detachment of the woman from the place of the victim — in relation to the development of political, social and legal discourses around gender issues in Argentina.
Keywords: Women's writing; Violence; Memory